AN ANALYSIS OF TRENDS AND PATTERNS OF SOCIAL SECTOR EXPENDITURE IN KARNATAKA - Suresha. A.L; Varadarajegowda. G.C; Venkatesh K.T. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Creating a Social Sector that is well developed influences a lot on the level of human development of an economy. In turn, the Social Sector can also play an essential role in affecting the amount of economic growth. A better quality of life results from the development of the social sector, which leads to higher productivity in the economy. The paper analyses trends and patterns of Social Sector Expenditure in Karnataka from 2003-04 to 2017-18. The study observes that, despite being low in proportion, the share of capital expenditure in Social Sector Expenditure has been increasing. The Education and Health sector is observed to be holding the highest share of Social Sector Expenditure in the state. The study concludes by suggesting for assessment of Social Sector Expenditure along with Human Development achieved over the period in the economy.